The Fight Over Freedom in 20th- and 21st-Century International Discourse Moments of ‘self-determination’ - Augestad Knudsen, Rita (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
VIII, 241 p. 1 illus.